Strategi Operasi untuk Memproduksi Produk Baru Pada PT Inkoasku - Erlinda Nusron Yunus; Nindya Yohana Debora (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to formulate the mission, objectives and strategy of operation or manufacturing for an automotive component factory that will produce a new product. The scope of this research is a case study at PT Inkoasku. Structured interviews were conducted with managers at PT Inkoasku related to customers and suppliers (external analysis) and quality, process, inventory, capacity, and supply chain (internal analysis). The questions are aimed at knowing the current external and internal operating conditions when only producing wheels and further needs when starting to produce disc’ as a new product. In addition to interviews, observations were also conducted on the operating system at PT Inkoasku. The results of external analysis show that the winner of orders from PT Inkoasku's operating system is price, while quality and delivery are order qualifications. Therefore, the operating strategies that can be applied include: choosing the type of batch process in running production, adding lean-six sigma in the quality system, automating the machine that will be used to produce disc’, optimizing the Material Requirement Planning (MRP) system and the min-max policy. in inventory management as well as mapping the procurement of goods and services and implementing Vendor-Managed Inventory (VMI) as a supply chain strategy. Keywords: operation management, operation strategy, manufacturing strategy, automotive component industry, QPICS